2003
DOI: 10.1016/s0014-5793(03)01183-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the blood group Lewisa determinant in the oviducal mucins of Xenopus tropicalis

Abstract: The amphibian Xenopus tropicalis appears an increasingly appealing model for both genetic and developmental biology studies, compared to the related species Xenopus laevis. Study of the glycosylation pattern of its secreted glycoproteins revealed that this species synthesizes large amounts of Lewis a epitope, whereas this motif has previously only been identi¢ed in animals within the primate lineage. The use of 1 H-nuclear magnetic resonance spectroscopy enabled us to resolve the sequence of three Lewis a -bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is possible that Msa FBP32 cross-links fucosylated glycans on bacteria or parasites35 to putative phagocyte receptors containing Le a , a blood group that may be also present in ectotherms36. Pre-exposure of E. coli to a binary tandem F-lectin from sea bass ( Dicentrarchus labrax ) significantly increases their phagocytosis by peritoneal macrophages relative to the unexposed bacteria, suggesting that F-lectins with multiple CRDs such as Msa FBP32 function as opsonins that mediate innate immune responses against microbial pathogens37.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that Msa FBP32 cross-links fucosylated glycans on bacteria or parasites35 to putative phagocyte receptors containing Le a , a blood group that may be also present in ectotherms36. Pre-exposure of E. coli to a binary tandem F-lectin from sea bass ( Dicentrarchus labrax ) significantly increases their phagocytosis by peritoneal macrophages relative to the unexposed bacteria, suggesting that F-lectins with multiple CRDs such as Msa FBP32 function as opsonins that mediate innate immune responses against microbial pathogens37.…”
Section: Discussionmentioning
confidence: 99%
“…It is also found in the conotoxin tx5a from Conus textile with an α linkage (α-D-Gal-(1→3)-α-D-GalNAc) to a threonine residue [ 41 ]. The terminal α-D-Gal-(1→3)-α-D-GalNAc motif is present in the egg jelly coat mucins of the amphibian X. tropicalis [ 42 ] and Bufo bufo [ 43 ], thus this motif is likely present in X. laevis as well. Therefore, the interaction between XCGL-1 and α-D-Gal-(1→3)-α-D-GalNAc is likely biologically relevant in X. laevis egg.…”
Section: Resultsmentioning
confidence: 99%
“…When this paper was in preparation, a report on the oligosaccharide determination from X. tropicalis egg jelly by NMR was published by Strecker et al In that study, eight neutral, one sulfated, and three sialylated oligosaccharides were identified. In this study, 16 neutral, 13 sulfated, and 6 sialylated oligosaccharides were found.…”
Section: Discussionmentioning
confidence: 99%